IMPLEMENTASI KEBIJAKAN PROGRAM WAJIB BELAJAR 9 TAHUN DI KABUPATEN BOGOR (Studi Kasus Kecamatan Cibinong Dan Kecamatan Sukamakmur) - Rikmanen Zidane; Rahmat Hidayat; Rudyk Nababan (JIAP (Jurnal Ilmu Administrasi Publik), 2021)
The importance of education for every citizen of Indonesia is to improve the quality of human beings with good character and morals, however, until now the problems regarding education are still not resolved. One of them is that the 9-year Compulsory Education policy is not evenly distributed throughout Indonesia, as happened in Bogor Regency which has guaranteed the implementation of compulsory education in all its regions, but there are still districts that have made the policy a success to date. This study aims to describe or describe the 9 Year Compulsory Education policy implemented in Bogor Regency, especially in Cibinong and Sukamakmur Districts. The method in this research is a descriptive method with a qualitative point of view. Regarding information retrieval techniques that researchers make using interviews, observation and documentation. Actions in data analysis are data reduction, data presentation, drawing conclusions and verification and using the theory of policy implementation from George C. Edward III which includes communication, resources, disposition and bureaucratic structures. The results of this study show that the implementation of the 9-year compulsory education in Bogor Regency is not evenly distributed in every district. This is because the communication carried out to the community is still not optimal, there is still a lack of available resources, and it is not maximized in carrying out tasks and the support of the bureaucratic structure that is still not optimal.